Sr 2 Fe 1+: X Re 1- x O 6 double perovskites: Magnetoresistance and (magneto)thermopower - Maignan, Antoine (2019)
Polycrystalline Sr2Fe1+xRe1-xO6 samples have been synthesized and structurally characterized by X-ray powder diffraction, transmission electron microscopy and X-ray absorption spectroscopy. Resistivity strongly increases with x, but a large and negative magnetoresistance persists up to x = 0.33. This is discussed considering the charge delocalization in iron and rhenium t2g orbitals.